(untitled) (Research, Society and Development, 2022)
The objective was to describe the epidemiological profile of hospitalizations and deaths in the Northeast region, comparing the pre-pandemic period with the post-pandemic period. This is a quantitative descriptive study carried out by collecting data from the Hospital Information System (SIH/SUS), available on the DATASUS platform, as well as literature selection from Pubmed, CAPES journal, and Google Academic. As results, it was found that in the pre-pandemic period (2018-2019) the number of hospitalizations was 385,103 and the number of deaths, 37,808, compared to the post-pandemic period (2020-2021), which was 340,555 and 36,490, respectively. The population that suffered most hospitalizations was the 60-69 age group, with 92,601 (24.04%) and 82,563 (24.24%) in the pre-pandemic and post-pandemic periods, respectively. The population that suffered the most deaths, on the other hand, was those older than 80 years, with 10,837 (28.6%) in 2018-2019 and 10,542 (28.89%) in 2020-2021. In the periods analyzed, Bahia and Pernambuco were the states with the highest absolute numbers of hospitalizations and deaths from CVD. Therefore, it becomes evident the need to analyze the impact of the pandemic on CVD to better treat the population of the epidemiological profile described above and avoid hospitalizations and reduce the number of deaths.